2018
DOI: 10.1111/ejn.14266
|View full text |Cite
|
Sign up to set email alerts
|

Pushing attention to one side: Force field adaptation alters neural correlates of orienting and disengagement of spatial attention

Abstract: Sensorimotor adaptation to wedge prisms can alter the balance of attention between left and right space in healthy adults, and improve symptoms of spatial neglect after stroke. Here we asked whether the orienting of spatial attention to visual stimuli is affected by a different form of sensorimotor adaptation that involves physical perturbations of arm movement, rather than distortion of visual feedback. Healthy participants performed a cued discrimination task before and after they made reaching movements to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 101 publications
(155 reference statements)
1
2
0
Order By: Relevance
“…Both groups recovered a reach precision close to baseline after four trials during POST-rotation and endpoint errors vanished with the same temporal pattern whatever the type of perturbation. Overall, adaptation to the new gravito-inertial force field appeared, in the present study, to have a similar effect on the sensorimotor system as in previous studies 27 , 36 , 37 , 52 , 59 , even though the mechanisms underlying sensorimotor adaptation might differ according to whether the perturbation is introduced gradually or abruptly 50 , 69 .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Both groups recovered a reach precision close to baseline after four trials during POST-rotation and endpoint errors vanished with the same temporal pattern whatever the type of perturbation. Overall, adaptation to the new gravito-inertial force field appeared, in the present study, to have a similar effect on the sensorimotor system as in previous studies 27 , 36 , 37 , 52 , 59 , even though the mechanisms underlying sensorimotor adaptation might differ according to whether the perturbation is introduced gradually or abruptly 50 , 69 .…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, reachability judgments were obtained before and after the action control system was updated as in our previous experiments 26 , 33 . Considering that previous studies reported that adaptation to gradually-altered limb dynamics also induces after-effects 36 , 50 , 52 , 53 , we predicted that exposure to gradual change in the Coriolis force would result in sensorimotor adaptation revealed by post-rotation after-effects on reaching movements, as typically observed after exposure to an abrupt change in Coriolis force. As mentioned before, such change typically influences the representation of the peripersonal space 26 , 33 , which was predicted here to not significantly differ between the pre-gradual rotation and the post-gradual rotation phases.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation